Injectable 0.19-mg fluocinolone acetonide intravitreal implant for the treatment of non-infectious uveitic macular edema - Weber, Lea F.; Marx, Stefanie; Auffarth, Gerd U.; Scheuerle, Alexander F.; Tandogan, Tamer; Mayer, Christian; Khoramnia, Ramin (Journal of ophthalmic inflammation and infection, 2019)
A retrospective observational clinical study to evaluate the safety and effectiveness of the injectable 0.19-mg fluocinolone acetonide intravitreal implant (ILUVIEN) in the treatment of non-infectious uveitic macular edema.
Gesehen am 20.09.2019